A pedagogy of possibility: Reading Roger Simon in the wake of Ferguson, Missouri. Issue 1 (1st January 2016) - Cassily, Shaleen; Clarke-Vivier, Sara
ABSTRACT: Recent examples of police brutality perpetrated against black bodies have called into question issues of class and race relations in the USA. State forms like schooling reconstitute social and racial inequities and allow the perpetuation of abuses. In this cultural moment, this essay turns to two texts by Roger Simon, Teaching Against the Grain and A Pedagogy of Witnessing to examine what it might mean to teach for engagement and solidarity, or what he calls a pedagogy of possibility. After a brief overview of the first book, we focus in on two particular sections, "Teachers as Cultural Workers" and "Pedagogy as Political Practice" to examine Simon's ideas regarding cultural work in public spaces as a precursor to freedom. Our purpose is to create a conceptual foundation upon which we can situate Simon's work in his second book. Then we examine the second book as an enactment of the first. Finally we turn to recent events in Ferguson, Missouri and the pedagogical outpouring of online materials attempting to "Teach Ferguson." Specifically, we analyze one online resource as a means to uncover an application of Simon's pedagogy of possibility in public space. It is our hope to situate Simon's work in this way in order to highlight specific cultural practices that promote social change.